2020
DOI: 10.1162/jocn_a_01585
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of Reward Memory during Sleep Does Not Require Dopaminergic Activation

Abstract: Sleep enhances memories, especially if they are related to future rewards. Although dopamine has been shown to be a key determinant during reward learning, the role of dopaminergic neurotransmission for amplifying reward-related memories during sleep remains unclear. In this study, we scrutinize the idea that dopamine is needed for the preferential consolidation of rewarded information. We impaired dopaminergic neurotransmission, thereby aiming to wipe out preferential sleep-dependent consolidation of high- ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Specifically, rather than a hypothetical friend, a second participant or confederate (either trustworthy or untrustworthy) in a similar design could be responsible for remembering "friend" items to determine how offloading behavior differs in the presence of another person compared with an imaginary friend. Lastly, participants were tested immediately after encoding, but future work could institute a distractor task between study and recall to examine whether the observed effects are maintained after a delay (see Asfestani et al, 2020;Spaniol, Schain, & Bowen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, rather than a hypothetical friend, a second participant or confederate (either trustworthy or untrustworthy) in a similar design could be responsible for remembering "friend" items to determine how offloading behavior differs in the presence of another person compared with an imaginary friend. Lastly, participants were tested immediately after encoding, but future work could institute a distractor task between study and recall to examine whether the observed effects are maintained after a delay (see Asfestani et al, 2020;Spaniol, Schain, & Bowen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Such an interaction between dopamine and reward was however not replicated in a study using a dopamine antagonist, with the re-test 22 hours after encoding. 4 Another study that included reward information, but additionally also emotional stimuli, 89 is discussed in the section "Studies with Multiple Cues of Future Relevance".…”
Section: Factors During Sleep Associated With Memory Performance Based On Reward Valuementioning
confidence: 99%
“…Indeed, in similar paradigms to ours dopamine-like medication has been associated with changes in enhanced memory persistence in healthy elderly ( Grogan et al, 2015 ) in a dose-dependent fashion ( Chowdhury et al, 2012 ), supporting the inverted U-shape hypothesis. Yet, others have found no impact of a dopamine agonist on verbal memory persistence ( Feld et al, 2014 ), or a dopamine d2-like receptor blocker ( Asfestani et al, 2020 ) on overnight reward consolidation in young adults. These differences in findings may be due to different medications or due to age-related reductions in dopamine neurons ( Carlsson et al, 1980 ; Kish et al, 1992 ; MacDonald et al, 2012 ) and/or slow-wave sleep duration, spindle counts and amplitudes ( Nicolas et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%